PERAN SEKOLAH DALAM MEMFASILITASI PENGGUNAAN GADGET POSITIF DAN PENANGGULANGAN CYBERBULLING DI KALANGAN SISWA SEKOLAH DASAR NEGERI (SDN) TASIKAPA RENDU TUTUBHADHA - Maria Diana Coo; Rodriques Servatius (Journal Education and Government Wiyata, 2026)
The use of gadgets among elementary school students has become an inseparable part of everyday life. Although technology offers educational benefits and wide access to information, its uncontrolled use can have negative impacts, in the form of addiction and the spread of cyberbullying cases. Various examples of cyberbullying actions are (1) spreading gossip or embarrassing personal information, (2) sending rude or threatening messages, (3) creating fake accounts to badmouth others, (4) creating content that mocks or insults. The driving factors for the spread of cyberbullying are (1) environmental influences, (2) imitation in the use of Facebook, (3) cyberbullying does not understand the impact of using social networks, (4) lack of attention from parents and teachers. This service aims to analyze the role of schools, including principals, teachers, and school committees, in encouraging the positive use of gadgets and the efforts made to overcome cyberbullying and social media ethics in elementary school environments.